Semaphorin 7a aggravates TGF-β1-induced airway EMT through the FAK/ERK1/2 signaling pathway in asthma - Peng, Haiying; Sun, Fei; Jiang, Yunxiu; Guo, Zihan; Liu, Xinyi; Zuo, Anli; Lu, Degan (Frontiers in Immunology, 2023)
Semaphorin 7a (Sema7a) plays a crucial role in regulating immune responses and initiating and maintaining TGF-β1-induced fibrosis. Transforming growth factor β1 (TGF-β1) can induce epithelial-mesenchymal transition (EMT) in primary airway epithelial cells (AECs). We hypothesized that Sema7a promotes TGF-β1-induced EMT in airway remodeling in asthma. The concentrations of Sema7a in the serum of asthmatic patients were detected by enzyme-linked immunosorbent assay (ELISA). The expression of Sema7a in the bronchus and its relationship to airway remodeling in an ovalbumin (OVA)-induced mouse model were examined. An integrin-β1 blocking antibody (GLPG0187) was used to reveal the interaction between Sema7a and integrin-β1. The protein levels of p-FAK and p-ERK1/2 were analyzed. Our study revealed that the level of sema7a was higher in the serum of patients with asthma than in that of healthy individuals. The expression levels of Sema7a and integrin-β1 were increased significantly in airway and lung tissues from the OVA-induced mice model of asthma. GLPG0187 inhibited not only TGF-β1-mediated EMT in human bronchial epithelial cells (HBECs) but also the proliferation of HBECs. The protein levels of p-FAK and p-ERK1/2 were subsequently decreased. Collectively, these data indicate that Sema7a may play an important role in airway remodeling by inducing EMT through the FAK and ERK1/2 signaling pathways in a mouse model of chronic asthma. New therapies for chronic asthma may be aided by the development of agents that target Sema7a.